O ensino de língua inglesa em uma escola pública de nível fundamental: realidade e perspectivas - CHAGAS, Ednaldo João das (UNIFAP – Universidade Federal do Amapá, 2022)
This study is directed theoretically in the field of Applied Linguistics. Situated in a foreign language, more specifically, the English language, it focuses on the teaching of language and moments of interaction in the classroom of the school Everaldo da Silva Vasconcelos Junior, located in Santana – AP. This qualitative ethnographic case study occurred from the restless wish of knowing how is the teaching of English in public fundamental schools of Amapá, since at this state borders, French language is very present. The results showed that English still prevails in the preference of the subjects studied. But many points need to be improved, especially when it comes to structure and material. It was also possible to detect that there is an awareness of teachers about the importance of foreign language in student education, so they make the best possible to make the school attractive and productive.